2015
DOI: 10.3389/fphys.2015.00016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of networks during absence seizure's on- and offset in rodents and man

Abstract: Network mechanisms relevant for the generation, maintenance and termination of spike-wave discharges (SWD), the neurophysiological hallmark of absence epilepsy, are still enigmatic and widely discussed. Within the last years, however, improvements in signal analytical techniques, applied to both animal and human fMRI, EEG, MEG, and ECoG data, greatly increased our understanding and challenged several, dogmatic concepts of SWD. This review will summarize these recent data, demonstrating that SWD are not primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 121 publications
(221 reference statements)
4
94
2
2
Order By: Relevance
“…the cortex was found to interact differently with the caudal and rostral part of the NRT) during SWDs and in a short period immediately prior to SWD onset, where the network already seems to prepare towards SWD generation. Based on these findings, different functional contributions of the different thalamic nuclei for SWD preparation, generation and maintenance, as well as a temporal SWD generation scenario was proposed (for review see (Luttjohann and van Luijtelaar, 2015)). …”
Section: Brain Regions Of Interestmentioning
confidence: 99%
“…the cortex was found to interact differently with the caudal and rostral part of the NRT) during SWDs and in a short period immediately prior to SWD onset, where the network already seems to prepare towards SWD generation. Based on these findings, different functional contributions of the different thalamic nuclei for SWD preparation, generation and maintenance, as well as a temporal SWD generation scenario was proposed (for review see (Luttjohann and van Luijtelaar, 2015)). …”
Section: Brain Regions Of Interestmentioning
confidence: 99%
“…As a fairly common form of generalized seizure, the network mechanisms of SWDs have been extensively investigated for more than seven decades (Avoli 2012;Luttjohann and van Luijtelaar 2015). Accumulating evidence indicates that SWDs are generated within the corticothalamocortical circuitry and that the dynamic interaction of local microcircuits within this neuronal network leads to the "full-blown" SWDs associated with absence epilepsy (McCormick and Contreras 2001;Steriade 2005;Huguenard and McCormick 2007;Luttjohann and van Luijtelaar 2015).…”
Section: Pathological Function Of Ca V 32 Channelsmentioning
confidence: 99%
“…Accumulating evidence indicates that SWDs are generated within the corticothalamocortical circuitry and that the dynamic interaction of local microcircuits within this neuronal network leads to the "full-blown" SWDs associated with absence epilepsy (McCormick and Contreras 2001;Steriade 2005;Huguenard and McCormick 2007;Luttjohann and van Luijtelaar 2015). The very early studies of absence epilepsy (also known as petit mal epilepsy) reported that SWDs, as in human absence epilepsy, could initiate and sustain after a brief electric stimulation in the thalamus in animals (Lewy and Gammon 1940;Lindsley et al 1949).…”
Section: Pathological Function Of Ca V 32 Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of GSWD using magnetoencephalography also revealed focal source in absence seizures (Tenney et al 2013;Westmijse et al 2009). These evidences suggest the possibility that some generalized seizures could be developed by a complex epileptogenic network involving both local and global brain networks (Blumenfeld et al 2003;Lüttjohann and van Luijtelaar 2015;McNally and Blumenfeld 2004). Furthermore, by interrupting the global network through corpus callosotomy (CC), several clinical studies have demonstrated the possibility of revealing focal seizure onset in scalp EEG (Clarke et al 2007;Hur et al 2011;Iwasaki et al 2011;Lin et al 2011;Ono et al 2011).…”
Section: Introductionmentioning
confidence: 98%